(3eaJGM GdTaGA (B( (3aj WH GdYjf (B)s - (3GHf GdfajS , YdGA GdOjf CHh GdMSf Ydj Hf CHj GdMRe GdbQTj, GHf GdfajS,J (B687 (3g` s
(3ChdgG (B:s
(3GdMeO dg edge GdMce , hehLO GdCTjGA ef HYO YOe aEf Yde GdWH ef CTQa GdYdhe , hEf ehVhYg HOf GdEfSGf , CTQa eG ai YGde Gdchf IGdaSGO s
(3BNQgG (B:s
(3bWhQ jfVL hjMdd , hjDNP eGA GdMdHI heGA GdHGHhfL hEcdjd Gdedc jWHN Edi Cf jbGQH GdGfYbGO hjQaY ai EfGA hjSJYed ai EfGA hjSJYed hbJ GdMGLI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B58s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B238 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS hGQi (B(3784) s
Keywords: (3GdWHs